The Orientalist Semiotics of Dune Religious and Historical References within Frank Herbert's Universe - Jacob, Frank (Büchner-Verlag, 2022)
Frank Herbert's »Dune« (1965) is considered to be one of the most successful Science Fiction novels of the 20th century. It introduces its readers to a future universe, in which the production of the most valuable resource of the universe - ›spice‹ - is only possible on one vast desert planet called Arrakis. »Dune« offers many different motifs, including a hero that eventually turns into a superhuman being. However, the novel is also rich of orientalist semiotics and relates to a sign system existent when Herbert wrote his book. Frank Jacob discusses these semiotics in detail and shows how much of »Lawrence of Arabia« is present in the story's plot.